Implementing the Agenda of the Namibian Ministry of Environment and Tourism : A Rapid Country Environmental Analysis with a Public Expenditure Review for Aligning Policy, Institutional and Financing Priorities - World Bank (Washington, DC, 2012)
This report is organized around three thematic chapters. Chapter one looks at the contribution of the environment and tourism sector to the Namibian economy as well as at some key achievements and challenges. Chapter two describes the policy and legislative framework, and the institutional analysis of the environment and tourism sector. Chapter three examines the financing of the sector and some key budget management issues. And finally in chapter four of volume one, a set of recommendations and short- and medium-term actions are proposed that aim to assist the Ministry in the implementation of its up-coming work programs as well as the strategic plan. Chapter four of volume two includes the assessment of the financing of the sector at the local level using the example of the Erongo Region.